The Øresund Traffic Forecast Model - Sørensen, Majken Vildrik; Nielsen, Otto Anker; Schauby, Jarn (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The Øresund Traffic Forecast Model was designed to forecast impacts of the fixed link crossing Øresund. The link connects the metropolitan area of Copenhagen with Malmö – the third largest city in Sweden. The link provides a direct rail and car connection between the two city-centres, previously only served by fast passenger boats. The latter was not connected to the rail network of Copenhagen, and parking facilities in Copenhagen near the boat was few and expensive. On the other hand several other ferry-lines connected other parts of the Copenhagen Region with the southern Sweden. Accordingly, the fixed link improved the connection between the two regions significantly – but to a varying extent for different parts of the region. The fixed link also improved the infrastructure for longer trips between the Scandinavian Peninsula and the European Continent. However, in this respect the link compete with quite a number of ferry links. From a modelling point of view, the task was difficult since the choice set included many overlapping routes and (sub-) mode-choices. For some trips, the link constitutes a significant improvement. But the link connects two countries, where culture, language and economy (e.g. labour legislation) provide a potential barrier for travel. Economic differences may also results in additional trips, e.g. shopping trips due to different VAT- and tax-levels on different goods. To model this context, tenders were invited for a large-scale traffic model project. The resulting model was in many respects state-of-the-art: A utility-based model (nested logit) was estimated from joint RP- and SP-datasets collected specifically for the study. Several sub-models (segments) were estimated for short- and long trips, and for different trip purposes. In addition, both passenger and freight traffic were described by different (sub) models. However, in reality the model failed to describe several impacts of the fixed link (as it turned out after the link opened). Especially, the model failed to describe the competition between fast boats and the rail link, and the magnitude of the social and economic barriers for short-distance traffic. Since the model itself is described in Øresundskonsortiet (2000) its structure is only briefly described in section 2 of the present paper. Accordingly, the main focus is on lessons learned from the model project, starting with a short description of the forecast results versus actual traffic in section 3. Section 4 describes different modelling issues that are considered as the main problem with conventional models. Finally, section 5 sums up the conclusions and provide some guidelines for future models of projects that involve a mixture of regional and international (long-distance) traffic.